Reducing Time Spent On Digitizing Quality Assurance and Control in Multifamily Construction Projects Using Safetyculture (Iauditor) - Agüero, Germán (2025)
This study evaluates the implementation of the digital platform Safety Culture (iAuditor) to optimize quality assurance and control (QA/QC) processes in multifamily construction projects, reducing time requirements and errors associated with traditional methods. Using a quasi-experimental approach, manual processes (pen-and-paper) were compared with real-time digital workflows, demonstrating that the tool eliminates redundant steps such as transcriptions and scanning, saving up to 60 minutes per inspection. Results showed significant improvements in efficiency, accuracy, and data accessibility, though challenges remain in externally coordinated activities. The proposed solution included staff training and customized digital form templates, highlighting its potential as a replicable model for the construction industry.